In-Situ Transmission X-Ray Microscopy Probed by Synchrotron Radiation for Li-Ion Batteries - Yang, Nai-Hsuan; Song, Yen-Fang; Liu, Ru-Shi (Frontiers in Energy Research, 2018)
Lithium-ion batteries are one of the main power sources for portable electronic devices and vehicles nowadays. However, the limitations of commercial cathode and anode materials cannot satisfy the increasing energy requirement of electronic devices. Therefore, investigating the chemistry and material changes during charge/discharge (lithiation/delithiation) is important to improve the properties of commercial LIBs. In-situ transmission X-ray microscopy has become one of the most important techniques for understanding the relationships between the electrode architecture and the cycling performance of electrode materials. In this mini-review, we are focus on the theory of the synchrotron transmission X-ray microscopy and pick up one of the most important reports to discuss the electrode material investigation.